Measuring Indonesian Cocoa Agroindustry Competitiveness from a Global Value Chain Perspective: Pengukuran Daya Saing Agroindustri Kakao Indonesia dari Perspektif Rantai Nilai Global - Dianawati; Nastiti S.I.; Andes Ismayana; Taufik Djatna; Indah Yuliasih (National Research and Innovation Agency, 2023)
Indonesian cocoa products in international trade face challenges in quality, food safety, and environmental requirements. Developing the cocoa agro-industry is essential to meet those global demands. The research aims to analyze the competitiveness of business in Indonesian cocoa products using the Global Value Chain (GVC), Revealed Comparative Advantage (RCA), and Trade Specialization Index (TSI) methodology. Research data uses the time series of Indonesian cocoa product export trade from 2001-2020. From a GVC perspective, the diversity of cocoa product exporters and the same competition drive a significant increase in competitiveness. Market access opportunities and regulatory support will encourage domestic industrial growth by utilizing efficient supply chains and making Indonesia part of the global production network. Cocoa products require economic value, from dry beans to ready-to-consume products. They are improving farmer’s bargaining position towards agro-industry institutions and better stakeholder coordination. The results of RCA show the comparative advantage of Indonesia cocoa exporters for HS code products 1801, 1802, 1803, 1804, and 1805 in the international market. The stages of identification of Indonesian cocoa products are the maturity stage for cocoa beans, the commercial maturity stage for cocoa paste and butter products, and the growth stage for cocoa product powder.